Alzheimer's disease: an epidemiological analysis over the number of hospitalizations and deaths in Brazil - Piovesan, Eduardo Cattapan; Freitas, Bruna Zanatta de; Lemanski, Francisco Costa Beber; Carazzo, Charles André (Arquivos de Neuro-Psiquiatria, 2023)
Background Alzheimer's disease (AD) is a neurodegenerative condition characterized by impaired cognitive function. It results in high morbidity, including a large number of hospitalizations, and mortality, generating high costs to health systems.Objective The present epidemiological analysis evaluated the number of hospitalizations and deaths by AD as the main diagnosis in Brazil between 2010 and 2020. This endeavor should contribute to a better understanding of the disease and its implications.Methods The present analytical, observational, longitudinal, and retrospective study used data extracted from the Department of Informatics of the Brazilian Unified Health System (DATASUS, in the Portuguese acronym). The variables include the number of hospitalizations, the total cost spent, the average cost per hospitalization, the average length of hospital stay, the number of deaths during hospitalization, the mortality rate per hospitalization, sex, age group, region, and race.Results From 2010 to 2020, there were 188,811 deaths and 13,882 hospitalizations for AD, with a total expenditure of BRL 25,953,019.40 in hospitalizations. The average length of hospital stay was 25 days. Over the considered period, mortality, the number of hospitalizations, and the total cost increased while the average length of stay decreased.Conclusion From 2010 to 2020, AD represented a large portion of hospital admissions, generating a significant cost to the health system and a large number of deaths. These data are important to undertake joint efforts to prevent hospitalizations of these patients in order to minimize impacts on the health system.
Keywords: Dementia; Alzheimer Disease; Epidemiology; Unified Health System; Brazil